A novel additive manufacturing-based technique for developing bio-structures with conformal channels and encapsulated voids. (17th November 2015) - Basalah, Ahmad; Esmaeili, Shahrzad; Toyserkani, Ehsan
Abstract: A novel additive manufacturing-based technique for developing bio-structures with conformal channels and encapsulated voids. The network of macro-channels in the structure of cortical bone is crucial, particularly for nutrition. Therefore, a successful bone implant should simulate the real bone architecture by including such channels in its structure. The introduction of additive manufacturing (AM) techniques in the orthopedic implant industry brings the potential of producing customized bone implants that mimic the structure of real bone. However, the depowdering issue in the powder bed AM technique has hindered the creation of macro-sized channels in bone implants composed of biocompatible materials. In this study, we introduce a new method for manufacturing implants which is composed of titanium and includes networks of channels. This technique is primarily based on printing individual components of a sliced structure, followed by depowdering and assembling the components before the sintering process. This new technique has the potential to control the internal features of 3D printed structures. A set of comparative physical and mechanical tests were conducted to characterize the resulting structures. Experimental characterization results showed that the shear strength of the sample that was made by the new technique was reduced by 24%–30%, where the porosity was slightly lower (∼2%) than that of a comparable control sample. However, the new technique had no effect on the compressive strength of the structure.